Analisis Usaha Tani Tumpang Sari Cabai Dan Tomat Terhadap Pendapatan Petani Di Desa Sikab - Deri Sudarto Ginting; Gustami Harahap (Universitas Medan Area, 2026)
This study aims to analyze the income level of farmers who apply the chili and tomato intercropping pattern in Sikab Village, and to identify internal and external factors that influence the income of the farm. In addition, this study also evaluates the efficiency of the intercropping pattern in increasing farmer productivity and profits. The study used a survey method, with direct interviews with farmers who apply the chili and tomato intercropping pattern. The sample was selected using the Simple Random Sampling method, with 21 farmers from a total population of 210 heads of families. The results of the analysis of the chili and tomato intercropping farming business in Sikab Village show that this farming system provides quite large benefits for farmers. Based on the calculation results, the average income obtained by farmers reached IDR 53,765,250.00 per hectare in one planting season, with a total cost of IDR 28,054,523.83 per hectare. Thus, the average income obtained by farmers in one planting season is IDR 25,710,726.17 per hectare. This study concludes that chili and tomato intercropping farmers in Sikab Village obtain quite good profits. Production cost efficiency can be increased with more optimal fertilizer and pesticide management, as well as government support in the distribution of agricultural facilities.